2000
DOI: 10.3989/cyv.2000.v39.i6.767
|View full text |Cite
|
Sign up to set email alerts
|

Materiales compuestos C/SiC para aplicaciones estructurales de alta temperatura. Parte I: estabilidad termodinámica y química

Abstract: El desarrollo de la industria aeroespacial se orienta actualmente hacia la tecnología hipersónica, el incremento en el rendimiento de las reacciones de combustión y la reducción de la emisión de contaminantes. Estos objetivos sólo pueden alcanzarse aumentando la temperatura de combustión, para lo cual es necesario desarrollar nuevos materiales que conserven sus propiedades mecánicas hasta temperaturas muy elevadas. Entre ellos se encuentran los materiales compuestos de matriz de SiC reforzada con fibra continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…It has been reported that in many processes, silica/carbon composites exhibit superior properties to their components separately, as result of a synergy between the properties of meso-ordered silica (elevated surface area and ordering in a wide range of porous structure) and the properties of active carbons (electrical conductivity, thermal stability, and easy modification of its surface chemistry by functionalization). 1 7…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in many processes, silica/carbon composites exhibit superior properties to their components separately, as result of a synergy between the properties of meso-ordered silica (elevated surface area and ordering in a wide range of porous structure) and the properties of active carbons (electrical conductivity, thermal stability, and easy modification of its surface chemistry by functionalization). 1 7…”
Section: Introductionmentioning
confidence: 99%
“…This is a one-step process that leaves the dimensions and geometry of the ceramic unaltered, creating materials that are well suited for use as catalyst supports in fuel cells, and in processes such as catalytic combustion or the purification of exhaust gases at high temperatures. Reaction mechanisms and equilibrium conditions can be inferred from the volatility diagrams of the various chemical species involved [3][4][5]. Here we present results for mullite (Al 6 Si 2 O 13 ), zircon (ZrSiO 4 ) and cordierite (Al 4 Mg 2 Si 5 O 18 ) ceramics, but the method can be extended to any other ceramic composed of two or more oxides with different stabilities under low-PO 2 atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Las propiedades de este material cerámico, y de los materiales compuestos de matriz SiC, hacen que se usen en la actualidad en multitud de aplicaciones: juntas mecánicas, válvulas… (componentes resistentes a la abrasión y a la corrosión); ventiladores cerámicos, elementos de calentamiento… (componentes resistentes a la temperatura); … (4,5).…”
Section: Introductionunclassified